49. Learning Objects and Instructional Design - Harvey, Brian (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2005)
Reusable learning objects are an approach that is receiving a significant amount of attention in distance-based and online education (see Reports # 11, 40, and 46 in this series). They have the potential to provide cost-effective, personalised instruction with a short development time. Instructional design principles, however, must play an important part in any such development effort, within a design process that occurs on two levels. At the higher level, instruction must be designed to deliver material efficiently to students at the modular/ course/ programme level. Design principles should be applied at the secondary level, at which the unique characteristics of learning objects are determined. Various instructional design (ID) methodologies are capable of dealing with these issues. The current report discusses a sle of these methodologies, and compares the ID adequacy of objects in four major learning object repositories: Merlot, CLOE, EOE, and Wisconsin Online. At the time of writing, each of these repositories contains objects that are inadequate from the ID point of view.